Perbandingan Hasil Belajar Matematika Siswa antara Penerapan Pendekatan Realistic Mathemtics Education dan Contextual Teaching And Learning - Upu, Hamzah; Mulbar, Usman; Purwanto, Indra (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2018)
The research type was an Quasi-experimental which involved two groups with different treatment. Objectives of this research were to know the differences in the improvement of students mathematics learning outcomes between the application of Realistic Mathematics Education approach and the application of Contextual Teaching and Learning approach. The population in this research was grade VII one of the Junior High School in Polewali Mandar, West Sulawesi and two experiment classes are selected by random technique as research sample. Data analysis by using descriptive and inferential statistics. The result was obtained there are not the different in the improvement of students mathematics learning outcomes between the application of RME approach and the application of CTL approach.